The Digital Bureaucracy Paradox: The Dilemma of Visionary Leadership in Balancing Work From Anywhere (WFA) Flexibility and Civil Servant Discipline at the Regional Secretariat of Sorong City - Anace Fransiska Jitmau; Rini Werdiningsih; Permadi Mulajaya (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
This research aims to conduct an in-depth analysis of the complex dynamics termed the "Digital Bureaucracy Paradox," a phenomenon that emerged significantly following the implementation of the Work From Anywhere (WFA) policy within the Regional Secretariat of Sorong City. The primary focus this study lies in the strategic dilemma faced by visionary leadership in balancing modern flexible work patterns with the obligation to enforce Civil Servant (ASN) discipline, which has historically been conventional and rigid. Amidst massive digital transformation, local-level bureaucracy is forced to adapt to work models requiring high agility, while simultaneously remaining bound by formalistic disciplinary regulatory standards. Quantitative findings indicate that although digital platforms have been effective as instruments for work instructions, the effectiveness visual supervision remains irreplaceable in maintaining the integrity of working hours, particularly regarding low scores in separating personal and professional matters during WFA. Conversely, submissions the E-Kinerja (E-Performance) system show very high level of administrative compliance, yet do not fully guarantee the quality of substantive outputs. Statistical analysis confirms that adaptive digital leadership has decisive influence on the successful implementation of the Electronic-Based Government System (SPBE). These findings offer  theoretical contribution to the study of bureaucratic behaviour within digital ecosystems and provide practical recommendations for redefining the ASN discipline from formalistic patterns toward a result-based substantive discipline. The synergy between visionary leadership and the strengthening of bottom-up accountability mechanisms through public participation is expected to realise a governance framework that is not only technologically modern but also functionally accountable in the post-pandemic era.